Efficacy of Oxaliplatin on Overall and Disease-Free Survival - Helwick, Caroline (MD Conference Express, 2008)
The results of the National Surgical Adjuvant Breast and Bowel Project (NSABP) C-07 trial [NCT00004931] demonstrated that oxaliplatin prolongs both progression-free and overall survival for patients with stage II or stage III colorectal cancer. The trial was designed to evaluate the efficacy of oxaliplatin when it was added to bolus 5-FU/leucovorin as adjuvant treatment.